2020
DOI: 10.1111/jac.12468
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of magnesium mitigates soil acidity stress in wheat

Abstract: Soil acidity is one of the most important soil constraints for wheat growth, and magnesium (Mg) can play a critical role in mitigating the adverse effects of soil acidity on plants. There is, however, limited information available about the influence of Mg nutrition, especially foliar application, on wheat (Triticum aestivum) growth in acidic soil. In a series of glasshouse experiments, Al‐sensitive wheat genotype (ES8) was grown to vegetative stage (Zadoks 23) with or without foliar Mg application at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
(42 reference statements)
3
12
0
Order By: Relevance
“…This can be interpreted as a consequence of applying Mg to soil in the form of MgSO 4 ·7H 2 O (due to the accompanying sulfate anion) 47 . Although the accompanying ion did not matter in foliar application, 28 it might be different in soil, where sulfate may complex Al in non‐toxic form 48 and contribute to greater shoot growth and Mg content in MgSO 4 ·7H 2 O‐amended plants compared with MgCl 2 ·6H 2 O‐amended plants (Fig. 1(b)).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This can be interpreted as a consequence of applying Mg to soil in the form of MgSO 4 ·7H 2 O (due to the accompanying sulfate anion) 47 . Although the accompanying ion did not matter in foliar application, 28 it might be different in soil, where sulfate may complex Al in non‐toxic form 48 and contribute to greater shoot growth and Mg content in MgSO 4 ·7H 2 O‐amended plants compared with MgCl 2 ·6H 2 O‐amended plants (Fig. 1(b)).…”
Section: Discussionmentioning
confidence: 99%
“…A similar response was reported in oregano ( Origanum vulgare ssp. hirtum ) 36 and Al‐sensitive wheat genotype, 28 where the plant growth increased significantly in response to foliar Mg application, when the plants were grown in acidic soil. Similar to Al‐sensitive genotype, applying foliar Mg also increased the growth of Al‐resistant genotype compared with zero foliar‐Mg‐treated plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies reported the beneficial effect of Mg spraying to relieve environmental stresses in crops, such as drought stress [ 29 ], heat stress [ 20 , 27 ], and soil acidity stress [ 54 ], and temperature [ 30 ] by improving the antioxidant metabolism and reducing the cell damages. During the drought stress, there is a reduction in the use of the energy captured in the photosynthesis reaction centers [ 55 ].…”
Section: Discussionmentioning
confidence: 99%